History and Dynamics of the Modern Boarding-School Darul Hikmah Tulungagung 1991-1998 - Shofiyah Romadhoni; Rizal Zamzami (Nur Science Institute, 2024)
This article discusses the history of the development of the modern Darul Hikmah Tulungagung Islamic boarding school 1991-1998. Darul Hikmah modern cottage was founded by KH. Nurul Hadi Ridwan located in Tawangsari village, Kedungwaru, Tulungagung. The establishment of the modern Darul Hikmah Islamic boarding school began with the Arabic and English language course institute founded by KH. Nurul Hadi Ridwan was also encouraged by his father's will to use the waqf land as an Islamic boarding school. The aims of this research to determine the development of learning programs at the Darul Hikmah modern boarding school which uses a combination of the government curriculum and the KMI Gontor curriculum. The research method in this study uses a historical method which consists of four stages, namely heuristics, verification, interpretation and historiography. The results of this research include: first, the early history of the establishment of the Darul Hikmah modern cottage in Tawangsari village in 1991 and the figures who played a role in it. Secondly, the development of the modern Darul Hikmah Islamic boarding school in 1991-1998 started with the implementation of educational programs, activities and facilities within the Islamic boarding school. Third, the implementation of a bilingual program which has been designated as the official language for daily communication among students as well as the language of instruction for formal education at the Darul Hikmah modern boarding school.